2000
DOI: 10.1016/s0014-5793(00)01719-1
|View full text |Cite
|
Sign up to set email alerts
|

Odorant and pheromone binding by aphrodisin, a hamster aphrodisiac protein

Abstract: Aphrodisin is a soluble glycoprotein of hamster vaginal discharges, which stimulates male copulatory behavior. Natural aphrodisin was purified and its post-translational modifications characterized by MALDI-MS peptide mapping. To evaluate its ability to bind small volatile ligands, the aphrodisiac protein was expressed in the yeast Pichia pastoris as two major isoforms differing in their glycosylation degree, but close in conformation to the natural protein. Dimeric recombinant aphrodisins were equally able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 44 publications
(53 reference statements)
3
39
0
Order By: Relevance
“…The molecular weight of the overexpressed Aphrodisin in the present study was ~17kDa, which is similar to earlier reports of molecular weight of natural aphrodisin of Syrian hamster (Singer et al, 1986;Magert et al, 1999;Briand et al, 2000). Peptide mass fingerprinting and matrix-assisted laser-desorption ionization-time-offlight (MALDI-TOF) mass spectra analysis of the trypsin digested ~17 kDa recombinant protein, and MS/MS analysis indicated that the overexpressed ~17 kDa protein was closely similar to aphrodisin of Syrian hamster (Figure-8 a-b).…”
Section: Tryptic Digestion and Mass-spectrometric Analysis Of The ~17supporting
confidence: 92%
See 1 more Smart Citation
“…The molecular weight of the overexpressed Aphrodisin in the present study was ~17kDa, which is similar to earlier reports of molecular weight of natural aphrodisin of Syrian hamster (Singer et al, 1986;Magert et al, 1999;Briand et al, 2000). Peptide mass fingerprinting and matrix-assisted laser-desorption ionization-time-offlight (MALDI-TOF) mass spectra analysis of the trypsin digested ~17 kDa recombinant protein, and MS/MS analysis indicated that the overexpressed ~17 kDa protein was closely similar to aphrodisin of Syrian hamster (Figure-8 a-b).…”
Section: Tryptic Digestion and Mass-spectrometric Analysis Of The ~17supporting
confidence: 92%
“…Lipocalins display a remarkable range of different molecular recognition properties and are variable in sequence, but share a typical 3D structure (Flower et al, 1993;Flower, 1995 and1996). Among lipocalins, aphrodisin is highly homologous (40% sequence identity) to rat odorant binding proteins OBP-1 and IF, expressed and secreted by nasal glands of rat in both sexes, which are thought to carry volatile hydrophobic odorants towards olfactory receptors across the aqueous nasal mucus (Pevsner et al, 1988;Briand et al, 2000). Aphrodisin has also 39% identity with a male-specific lipocalin (MSP) expressed in submandibular glands of male hamster, which is secreted in saliva (Thavathiru et al, 1999;Srikantan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, once cleaved from the glutamine residue as shown in this work, the acids might subsequently associate non-covalently with apolipoprotein D, and this non-covalent association could be just one more mechanism of slow release of these volatiles from the axilla. A similar release mechanism is postulated for hamster aphrodisin and a putative hydrophobic pheromonal compound (29). Finally, apoD has an N-terminal glutamine residue (15), and we cannot rule out the possibility, that a covalent linkage to this residue exists and that the proteins are first cleaved by an endopeptidase thus releasing the terminal acid-Gln conjugate.…”
Section: Discussionmentioning
confidence: 87%
“…However, the general view is that these volatile ligands need to be transported into the VNO by transport proteins belonging to the lipocalin family; in vivo, such molecules gain access to the VNO after direct contact with the stimulus source. Among these proteins that act as carrier for volatile ligands, some, such as major urinary proteins (MUPs) [15,40] or aphrodisin [17] have been now clearly characterized. It should be noticed that these carrier proteins might also serve by themselves as cues for individual recognition, especially because they exhibit a high degree of polymorphism [40] and are able to stimulate egr-1 expression in specific regions of the accessory olfactory bulb [16].…”
Section: Functional Roles Of Both the Main And The Accessory Olfactormentioning
confidence: 99%